'Noobs' and 'chicks' on Animutation Portal: power and status in a community of practice. (17th July 2008) - Kendall, Lori
Researchers interested in knowledge communication within communities of practice tend to focus on tasks, skills, or the shared interests of the group, while relegating other aspects of interaction and communication to the 'cultural context'. But from a participant perspective, knowledge communication includes knowledge about group culture and identity. Attention to participant perspectives and motivations provides a better understanding of what counts as knowledge and how knowledge communication is accomplished. This paper analyses communication within a voluntary community of practice oriented towards a hobby activity. Animutation is a subgenre of amateur animated online videos. Participants in the animutation subculture are primarily US-based young men who interact on a variety of websites that offer video hosting and bulletin board services. In this paper, I analyse discussion posts to the website animutationportal.com. In addition to the specific cultural context of the animutation subculture, participants' identities and understandings of other social contexts (such as the culture of online video production in general) influence their interaction and knowledge communication. While issues of belonging and culture are likely more explicit in voluntary, leisure-oriented communities of practice such as the animutation subculture, these aspects of community participation are important to consider in all communities of practice.